2014
DOI: 10.1016/j.wem.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Wilderness Medical Society Practice Guidelines for Basic Wound Management in the Austere Environment: 2014 Update

Abstract: In an effort to produce best-practice guidelines for wound management in the austere environment, the Wilderness Medical Society convened an expert panel charged with the development of evidence-based guidelines for the management of wounds sustained in an austere (dangerous or compromised) environment. Recommendations are made about several parameters related to wound management. These recommendations are graded based on the quality of supporting evidence and the balance between the benefits and risks or burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 139 publications
0
28
0
Order By: Relevance
“…9 The Wilderness Medical Society latest practice guideline on basic wound management recommends high-pressure irrigation (6-15 psi), especially in the case of open fractures. 10 Low pressure, in this expert consensus, was o6 psi and very high pressures were 415 psi. A 2015 study investigating irrigation of open fractures categorized 3 pressure groups based on the pulsed lavage and handheld, battery-operated irrigators used in the operating room: high pressure (420 psi), low pressure (5-10 psi), and very low pressure (1-2 psi).…”
Section: Discussionmentioning
confidence: 72%
“…9 The Wilderness Medical Society latest practice guideline on basic wound management recommends high-pressure irrigation (6-15 psi), especially in the case of open fractures. 10 Low pressure, in this expert consensus, was o6 psi and very high pressures were 415 psi. A 2015 study investigating irrigation of open fractures categorized 3 pressure groups based on the pulsed lavage and handheld, battery-operated irrigators used in the operating room: high pressure (420 psi), low pressure (5-10 psi), and very low pressure (1-2 psi).…”
Section: Discussionmentioning
confidence: 72%
“…This is no longer the case given that application of commercial tourniquets for life-threatening arterial bleeds is now considered the primary intervention to save lives in austere environments. As with tourniquet application in the operating room, there is minimal risk of complication related to placement for up to two hours in a field environment (Ostman et al 2004; Quinn et al 2014; Tourtier et al 2013). Additionally, a review conducted in the Journal of Trauma and Acute Surgery in 2015 found that improvised tourniquets were as capable as commercial tourniquets in stopping arterial bleeding, although they tend to be more painful (Stewart et al 2015).…”
Section: Myth 8: the Myth Of Tourniquet Dangermentioning
confidence: 99%
“…There has only been one study on the efficacy of pressure points, and it found them lacking in comparison to other approaches. In practice, pressure points are extremely difficult to locate and apply for any period of time; the utility of this technique is a myth and it is no longer recommended (Drew et al 2015; Quinn et al 2014). There are no studies measuring the effectiveness of limb elevation to assist in hemorrhage control, but as there is little risk and some value, doing so is recommended as long as it does not delay or complicate the delivery of direct manual pressure, application of pressure dressings, or application of a tourniquet.…”
Section: Myth 10: Wound Management Mythsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a multitude of published studies on the subject, friction blisters remain a common and debilitating injury among participants in wilderness and outdoor pursuits, and there remains no widespread consensus on effective prevention strategies. 14,[16][17][18] We conducted a systematic search and qualitative analysis of prospective controlled trials to determine if sock, antiperspirant, or barrier strategies were effective in prevention of friction blisters of the foot in wilderness and outdoor pursuits.…”
Section: Introductionmentioning
confidence: 99%